2004
DOI: 10.1111/j.1440-1754.2004.00317.x
|View full text |Cite
|
Sign up to set email alerts
|

What affects the age of first sleeping through the night?

Abstract: Little of the variation between children in age of first sleeping through the night could be explained by these nine factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The Consumer Product Safety Commission (CPSC) in 1999, being one of many sources to recommend against co-sleeping, concluded that it was a risk factor for SIDS (Nakamura, Wind, & Danello, 1999); however, some researchers have argued that co-sleeping is actually protective against SIDS (Adams, Jones, Esmail, & Mitchell, 2004;Latz, Wolf, & Lozoff, 1999;McKenna, 1996;Mosko, Richard, McKenna, Drummond, & Mukai, 1997). For example, with the positive association between co-sleeping and the incidence of breastfeeding throughout infancy (e.g., Ball, 2003;Hayes, Roberts, & Stowe, 1996;Okami, Weisner, & Olmstead, 2002), co-sleeping may be protective against SIDS because breastfeeding alone has been shown to be correlated with a reduced risk of SIDS (McKenna & Mosko, 1994;McKenna et al, 1997).…”
Section: Review Of the Literature On Correlates Of Infant Co-sleepingmentioning
confidence: 99%
“…The Consumer Product Safety Commission (CPSC) in 1999, being one of many sources to recommend against co-sleeping, concluded that it was a risk factor for SIDS (Nakamura, Wind, & Danello, 1999); however, some researchers have argued that co-sleeping is actually protective against SIDS (Adams, Jones, Esmail, & Mitchell, 2004;Latz, Wolf, & Lozoff, 1999;McKenna, 1996;Mosko, Richard, McKenna, Drummond, & Mukai, 1997). For example, with the positive association between co-sleeping and the incidence of breastfeeding throughout infancy (e.g., Ball, 2003;Hayes, Roberts, & Stowe, 1996;Okami, Weisner, & Olmstead, 2002), co-sleeping may be protective against SIDS because breastfeeding alone has been shown to be correlated with a reduced risk of SIDS (McKenna & Mosko, 1994;McKenna et al, 1997).…”
Section: Review Of the Literature On Correlates Of Infant Co-sleepingmentioning
confidence: 99%
“…At about 10–12 weeks of age, the first signs of a circadian rhythm begin to develop, marked by an increased ease of sleeping through the night 2. The change in total sleep duration over 24 hours continues and decreases from 16 to 17 hours in newborns, to 14–15 hours at 16 weeks of age, and 13–14 hours by 6 months of age 3,4. While the need for day sleep decreases,5 night sleep duration increases through the first year of life,57 resulting in a shift towards more nocturnal patterns of sleep.…”
Section: Introductionmentioning
confidence: 99%
“…Co-sleeping was reported to postpone the age of the first infant's sleeping through the night (Adams, Jones, Esmail, & Mitchell, 2004). Regular bed-sharing with parents led to more disruptive sleep and an increased number of night awakenings in young children (Lozoff, Askew, & Wolf, 1996;Madansky & Edelbrock, 1990), as well as to enhanced arousals (McKenna, Mosko, Dungy, & McAninch, 1990).…”
Section: Sleeping In the Parental Bedmentioning
confidence: 96%